The Black studies reader - Bobo, Jacqueline; Hudley, Cynthia; Michel, Claudine (Routledge, 2004)
Black studies emerged from the tumultuous social and civil rights movements of the 1960s and empowered African Americans to look at themselves in new ways and pass on a dignified version of Black history. However, it also enriched traditional disciplines in profound and significant ways. Proponents of Black and ethnic studies confronted the false notion that scholarly investigations were objective and unbiased explorations of the range of human knowledge, history, creativity, artistry, and scientific discovery. As they protested against hegemonic notions like universal psychology and re-evaluated canonical texts in literature, a new model of academic inquiry evolved: one committed to serving a range of populations, that critiqued traditional politics, culture, and social affairs, and worked with activist energy for the transformation of the existing social order. With an all-star cast of contributors, The Black Studies Reader takes on the history and future of this multi-faceted academic field. Topics include Black feminism, cultural politics, Black activism, lesbian and gay issues, African American literature and film, education, and religion. This authoritative collection takes a critical look at the current state of Black studies and speculates on where it may go from here.
Keywords: LGBTQIA2+; afro-féminisme; amériques; approches et analyses; féminisme islamique; histoire et politique; identités LGBTQIA2+; militance; outils; ouvrages de références; racisme; ressource en ligne; régions géographiques; sexualité; système colonial; systèmes d'oppressions; thématiques; états-unis

Militantisme et recherche féministe au Québec - Descarries, Francine (Labrys (en ligne), 2004)
Keywords: SAC; amériques; approches et analyses; histoire et politique; incomplet; militance; québec; rapports sociaux de sexe; recherche partenariale; ressource en ligne; régions géographiques; thématiques

Stolen From Our Bodies: First Nations Two-Spirits/Queers and the Journey to a Sovereign Erotic - Driskill, Qwo-Li (Studies in American Indian Literatures, 2004)
Keywords: 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; amériques; approches et analyses; autothéorie; cherokee; cours; discipline; féminisme autochtone; militance; premier cycle; premières nations; périodes historiques; queer; régions géographiques; sexualité; soc2014; système colonial; systèmes d'oppressions; thématiques; états-unis

Femmes et pouvoirs : à la conquête des territoires - Institut de recherches et d'études féministes (FéminÉtudes, 2004)
Cette publication aborde les conquêtes passées et en cours pour l’accès au pouvoir des femmes. *** FéminÉtudes est une revue étudiante, féministe et multidisciplinaire. La revue est née en 1995 de l’initiative d’étudiantes féministes dans l’intérêt de partager leurs recherches et de créer un groupe affinitaire. La revue est dirigée par des collectifs de rédaction bénévoles et autogérés, et soutenue par l’Institut de Recherches en Études Féministes (IREF) de l’Université du Québec à Montréal. Au fil des ans, FéminÉtudes a réussi à se bâtir une réputation et une légitimité dans le champ de la recherche en études féministes, tout en offrant une tribune au travaux et aux réflexions de dizaines d’étudiant.e.s. Au-delà de la recherche, c’est également pour l’avancement des luttes féministes que FéminÉtudes souhaite continuer à grandir.
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; corps; droits des femmes*; espace public; féminétudes; histoire et politique; militance; pouvoir; périodes historiques; québec; ressource en ligne; régions géographiques; thématiques

Namaji: Two-Spirit Organizing in Montreal, Canada - Meyer-Cook, Fiona; Labelle, Diane (Journal of Gay & Lesbian Social Services, 2004)
This article traces the authors' involvement in Two-Spirit organizing in Montreal since 1995. The term Two-Spirit is often used by lesbian, gay, bisexual and transgendered (LGBT) people of Aboriginal descent in both the U.S. and Canada. The authors explore the multifaceted aspects of organizing within a Two-Spirit community. They begin with an examination of contemporary challenges facing Two- Spirit people within Canadian society and then provide several concrete examples of local organizing, ranging from the creation of an educational video on HIV/AIDS and participation in a collaborative project with a school of social work to national and international alliance-building.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; amériques; approches et analyses; canada; cours; discipline; féminisme autochtone; histoire et politique; militance; montréal; personnes bispirituelles; premier cycle; périodes historiques; queer; régions géographiques; sciences humaines; soc2014; thématiques; travail social; études gaies et lesbiennes

Organizational "emotion work" through consciousness-raising: An analysis of a feminist organization - Reger, Jo (Qualitative Sociology, 2004)
In this article I explore how organizational processes link to certain emotional responses, as a way of investigating more fully the role emotions play in social movements. Through the construction of a case study of a feminist group, the New York City chapter of the National Organization for Women (NYC NOW), I analyze how certain emotions, such as anger, alienation, hopelessness and frustration, are redefined within an organizational context. I find that consciousness-raising serves as the organizational process that helps transform personal emotions into a collectively defined sense of injustice. This transformation has the potential of creating actors dedicated to chapter activism.
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; care; discipline; militance; mouvements féministes; new york; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; sociologie; thématiques; émotions; états-unis; étude qualitative

Creating emotional resonance: Interpersonal emotion work and motivational framing in a transgender community - Schrock, Douglas; Holden, Daphne; Reid, Lori (Social Problems, 2004)
In this article, we examine how interpersonal emotion work in a transgender support group and motivational framing of transgender social movement organizations together constructed favorable conditions for emotional resonance. We define emotional resonance as the emotional harmony and/or disjuncture between collective action frames and the emotional lives of potential recruits. Data derive from fieldwork, interviews, online e-mail lists and forums, community publications, activist speeches, and social movement organizations' recruitment appeals. Transgendered people joined support groups hoping to find relief from shame, fear, powerlessness, alienation, and inauthenticity. Although group members' emotion work partly accomplished such relief, it was hindered by identity conflicts and the temporal bounds of the meetings. Transgender activists and nascent social movement organizations, however, used motivational framing to promise targeted recruits a more permanent emotional resolution—one which could draw them into the movement. Our analysis moves transgender scholarship beyond issues of identity and moves framing theory beyond an almost exclusive concern with cognitive processes.
Keywords: 1900-1999; 1990-1999; LGBTQIA2+; amériques; care; identités LGBTQIA2+; militance; mouvements sociaux; personnes trans*; périodes historiques; ressource en ligne; régions géographiques; thématiques; émotions; états-unis